2004
DOI: 10.1038/modpathol.3800206
|View full text |Cite
|
Sign up to set email alerts
|

Ets-1 transcription factor is widely expressed in benign and malignant melanocytes and its expression has no significant association with prognosis

Abstract: Ets-1 transcription factor has been associated with tumor progression in various carcinomas, but its expression in malignant melanoma was only recently described. The study was conducted in two steps: exploratory and confirmatory. In the first step, we studied 69 primary melanomas, 28 metastatic melanomas, 10 usual intradermal nevi and 13 various melanocytic skin lesions. In the second step, an additional group of 98 patients with follow-up of up to 200 months was also evaluated. Immunohistochemical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…In melanoma, the levels Ets-1 were similarly found to be higher than those in benign melanocytic lesions and melanocytes, and to increase with progression of the disease (Poser and Bosserhoff, 2004; Rothhammer et al , 2004; Torlakovic et al , 2004). Consistently, the results in this study also showed that Ets-1 was commonly expressed at high levels in fresh melanoma isolates.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In melanoma, the levels Ets-1 were similarly found to be higher than those in benign melanocytic lesions and melanocytes, and to increase with progression of the disease (Poser and Bosserhoff, 2004; Rothhammer et al , 2004; Torlakovic et al , 2004). Consistently, the results in this study also showed that Ets-1 was commonly expressed at high levels in fresh melanoma isolates.…”
Section: Discussionmentioning
confidence: 91%
“…Increased Ets-1 expression has been reported to correlate with grade of malignancy and poorer prognosis in a number of cancers (Davidson et al , 2001; Span et al , 2002). In melanoma, high levels of Ets-1 are often associated with progression of the disease (Poser and Bosserhoff, 2004; Rothhammer et al , 2004; Torlakovic et al , 2004). The role of Ets-1 in regulation of apoptosis seems to be cell type-dependent, as it protects against apoptosis in some cell types, but induces apoptosis in others (Bories et al , 1995; Sato et al , 2001; Teruyama et al , 2001; Dittmer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ETS‐1 is expressed in melanocytes migrating from the neural crest during embryogenesis and in normal adult melanocytes, but its role in malignant melanomas appears controversial. ETS‐1 has been reported either as a valuable diagnostic/prognostic marker (Rothhammer et al., 2004) or as molecule with no clear association with clinical outcome (Torlakovic et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ets-1 is expressed at high levels in many types of cancers and is involved in many biological processes in cancer cells such as cell growth and survival (Davidson, et al, 2001;Span, et al, 2002). In melanoma, the levels Ets-1 were similarly found to be higher than those in benign melanocytic lesions and melanocytes and to increase with progression of the disease (Rothhammer, et al, 2004;Torlakovic, et al, 2004). Although the role of Ets-1 in regulation of apoptosis may vary between different cell types, transcriptional up-regulation of Mcl-1 by Ets-1 in melanoma cells subjected to ER stress indicates that it is critical in protection of melanoma cells against ER stress-induced apoptosis (Dong, et al, 2011).…”
Section: Up-regulation Of Mcl-1 Is Critical For Survival Of Melanoma mentioning
confidence: 89%